2017
DOI: 10.1007/s00520-017-3976-1
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin for febrile neutropenia prophylaxis in acute myeloid leukemia patients associated with reduction in hospital admissions

Abstract: Prescribing oral levofloxacin post-consolidation chemotherapy in AML patients is associated with a reduction in febrile neutropenia. Further research is required to identify the impact on fluoroquinolone resistance and risk of CDAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
0
12
0
1
Order By: Relevance
“…36,37 The need for fluoroquinolone prophylaxis also in AML patients has been considered. 26,38,39 In the study by Castañón et al, 40 fluoroquinolone prophylaxis reduced the incidence of Gram-negative bacterial infections during the TA B L E 4 Factors affecting Sequential (Sepsis-related) Organ Failure Assessment (qSOFA) score (qSOFA score ≥ 1 and qSOFA score ≥ 2), and predictors for intensive care unit (ICU) admission and infectious mortality during FN in 355 febrile neutropenia periods of 125 AML patients consolidation treatments. The other side of the coin is the threat of multidrug resistance, which has even been reported to influence the clinical course of AML.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 The need for fluoroquinolone prophylaxis also in AML patients has been considered. 26,38,39 In the study by Castañón et al, 40 fluoroquinolone prophylaxis reduced the incidence of Gram-negative bacterial infections during the TA B L E 4 Factors affecting Sequential (Sepsis-related) Organ Failure Assessment (qSOFA) score (qSOFA score ≥ 1 and qSOFA score ≥ 2), and predictors for intensive care unit (ICU) admission and infectious mortality during FN in 355 febrile neutropenia periods of 125 AML patients consolidation treatments. The other side of the coin is the threat of multidrug resistance, which has even been reported to influence the clinical course of AML.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…The frequency of Gram‐negative bacteremia, for example, Escherichia coli , known to be associated with substantial mortality, has increased as a cause of sepsis 36,37 . The need for fluoroquinolone prophylaxis also in AML patients has been considered 26,38,39 . In the study by Castañón et al, 40 fluoroquinolone prophylaxis reduced the incidence of Gram‐negative bacterial infections during the consolidation treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the true benefit of levofloxacin prophylaxis in preventing FN in intermediate-risk patients may also be smaller than described, leaving us underpowered to adequately assess the impact of body size on FN in this study. As the benefit of levofloxacin prophylaxis has been best described in high-risk groups, [8][9][10][11][12][13][14][15][16] future studies in high-risk populations might be better suited to assess the impact of body size on FN during levofloxacin prophylaxis. Lastly, FN may be attributable to factors that are not related to the adequacy of prophylaxis regimens.…”
Section: Discussionmentioning
confidence: 99%
“…We teremia with and without prophylaxis. 1,2,4,7,[11][12][13][14][15][16][17] Published literature was used to estimate the probability of ICU admission or death, with or without bacteremia. 4,5,11,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The probability of levofloxacinrelated adverse events was estimated using the FDA-approved package insert.…”
Section: Model Parametersmentioning
confidence: 99%
“…Egan et al noted differences in findings may be due to more strict inclusion criteria and analysis of more recently published trials in the former 54. Multiple studies have found no increased risk in Clostridium difficile infection with levofloxacin prophylaxis, with some studies even noting a significant decrease in infection rates 7,14,56. Despite concerns regard-ing fluoroquinolone exposure in pediatric patients, long-term results of an observational surveillance study of over 1000 children on phase III trials found the medication was well tolerated overall.…”
mentioning
confidence: 99%